INFLUENCE OF THE CONSUMPTION OF CARBONATED BEVERAGES IN THE PREVALENCE OF DENTAL EROSION IN YOUNG BASKETBALL PLAYERS - Vladimir Lara A; Maria José Jarrin; Olivia Toalombo; Alex Carrera; Dourado Logersio Alessandro; Ana del Carmen Armas (Kiru)
Objective: To assess the prevalence of dental erosion among basketball players who report consumption of carbonated beverages. Materials and methods: a cross-sectional study is proposed in a population of 60 basketball players aged 8 to 18 years, who perform physical activity more than 3 times a week and who consume energy drinks more than 3 times a week, without syndromes or systemic disease neither physical or intellectual disability. The participants were examined clinically by a single examiner regarding their upper anterior teeth through BEWE tooth erosion index and also by a questionnaire on knowledge and consumption of acidic beverages. Results: a high prevalence of dental erosion was observed (56.6%) in the evaluated population; 41.67% of participants preferred to consume hydrating drinks after the training day, with a high percen tage of carbonated beverages per day; where 71.67% know the negative effects of the consumption of these drinks. Conclusion: The presence of alterations in dental structure in the evaluated population is high.